2002
DOI: 10.1021/ja004010b
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bonds by Mechanical Stress:  When Do Electrons Decide for the Other Side?

Abstract: Using first-principles molecular dynamics, we have simulated reactions that can be induced by mechanical stress in a polymer. We have stretched a small piece of poly(ethylene glycol) (PEG) in water at finite temperature. Both the molecule and the solvent were described quantum mechanically on an equal level. The formation of ions was observed, which corresponds to a heterolytic bond cleavage. We were able to monitor the motion of the electrons during the reactions. Our simulations show that the electron transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 51 publications
7
83
1
3
Order By: Relevance
“…23,24 As pointed out in previous studies, 14,18 small microruptures, which are frequently observed in the force-distance curves of the amino-linked CMA, clearly indicate that a bond within the surface linker is indeed breaking in this experimental system. Within this surface linker, the carboxylic acid amide bond (C(O)-N), and the siloxane bond (Si-O) are both hydrolysable in aqueous environments.…”
Section: Resultssupporting
confidence: 73%
“…23,24 As pointed out in previous studies, 14,18 small microruptures, which are frequently observed in the force-distance curves of the amino-linked CMA, clearly indicate that a bond within the surface linker is indeed breaking in this experimental system. Within this surface linker, the carboxylic acid amide bond (C(O)-N), and the siloxane bond (Si-O) are both hydrolysable in aqueous environments.…”
Section: Resultssupporting
confidence: 73%
“…113 It is also conceivable that mechanical forces may increase the dissociation rate of adsorbed water by disconnecting hydrogen bonds of, e.g., the autodissociation transition states of water, which under normal conditions in most cases does not separate into two water ions. 116 Simulations have also indicated that adsorbed water may enhance the heterolytic mechanical breaking of chemical bonds, 117 and it has been suggested that adsorbed water molecules may be decomposed tribochemically into hydrogen radicals and a hydroxyl anions by emitted triboelectrons. 109 A quantification of these mechanisms would be important for differentiating between water-based versus water-enhanced charging mechanisms.…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
“…During these simulations, F is applied by increasing the distance between a pair of atoms at a constant velocity. They have used this approach to explore the changes in electronic structure that occur when solvated polymers are stretched to the point of rupture [41]. Their studies showed that bond rupture occurred through a heterolytic process involving solvent molecules.…”
Section: Application Of F Through Constrained Geometriesmentioning
confidence: 99%
“…These studies have focused primarily on simulating molecular systems exposed to external forces by treating the system as though it moves on a force-modified potential energy surface that incorporates the work performed on a chemical system as it undergoes structural changes in the presence of an external force. These studies have examined the rupture forces of bonds [32], the reactivities of molecules subjected to tensile stresses and strains [38][39][40][41], the effects of strains on pericyclic reactions [14, 29-31, 33, 34, 42-44], the differences between thermochemistry and mechanochemistry [45], and the effects of chain length on the transduction of external forces at atomic levels [46,47].…”
Section: Introductionmentioning
confidence: 99%